Peningkatan Kemampuan Menulis Cerpen melalui Penerapan Model Pembelajaran Berbasis Proyek pada Siswa Kelas V SDN Centre Mawang Kabupaten Gowa - Andi Anugrah Sucilia Ramadhan; Aco Karumpa; B. Syukroni Baso (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The main problem in this study is how the application of project-based methods can improve the short story writing skills of fifth-grade students at SDN. Centre Mawang. This study aims to improve students' writing skills through the application of project-based learning models in fifth-grade students at SDN. Centre Mawang. The type of research used in this study is descriptive classroom action research (CAR). Which consists of two cycles where each is carried out for 4 meetings. The research procedures include planning, implementation, action, observation and reflection. The subjects in this study were 33 fifth-grade students at SDN. Centre Mawang. Based on the results of the study, it can be concluded that the ability to write short stories through the application of project-based methods can significantly improve short story writing in the Indonesian Language subject in fifth-grade students at SDN Centre Mawang. With student completion in the cycle 1 test of 50% and in the final test of cycle II of 99%, it can be said that the students' learning outcomes have reached the completion criteria. The conclusion of this study is that the application of project-based learning models is effective in improving students' short story writing skills. Through learning activities involving the planning, creation, and completion of short story writing projects, students become more active, creative, and focused in their writing process. This is evident in the improved quality of their writing and their learning completion in each research cycle. Therefore, the project-based learning model can be used as an alternative learning strategy to improve short story writing skills in elementary school students.